Rethinking rice reserves: Policy pathways for stability amid market turbulence - Mirzabaev, Alisher; Pede, Valerien; Basnet, Shyam (International Rice Research Institute, 2025)
Highlights • From panic to glut, rice market volatility persists: After the 2023 price spike, record harvests and overflowing stocks have driven international rice prices to multiyear lows, squeezing farm incomes and intensifying competition among exporters. • Supporting stable and well-managed rice reserves: There is a need to set risk-based reserve targets, separate emergency buﬀ ers from price support stocks, enforce countercyclical release triggers, and crowd in private storage; applying these principles will help protect farmers and consumers while minimizing fiscal overhangs. It is crucial that rice reserves are managed to smoothen cycles rather than amplify price volatility. • Regional pathways to more stable rice markets: Countries can look into upgrading regional arrangements, such as the ASEAN Plus Three Emergency Rice Reserve (APTERR) to a fast-trigger facility with a modest permanent stock and a cash window, tying access to timely stock and harvest data, and backstopping this with transparent data and trade protocols so that shocks do not snowball across markets.